Estimated human health risks from recreational exposures to stormwater runoff containing animal faecal material. (October 2015) - Soller, Jeffrey; Bartrand, Timothy; Ravenscroft, John; Molina, Marirosa; Whelan, Gene; Schoen, Mary; Ashbolt, Nicholas
Abstract: Scientific evidence supporting recreational water quality benchmarks primarily stems from epidemiological studies conducted at beaches impacted by human fecal sources. Epidemiological studies conducted at locations impacted by non-human faecal sources have provided ambiguous and inconsistent estimates of risk. Quantitative Microbial Risk Assessment (QMRA) is another tool to evaluate potential human health risks from recreational exposures to non-human faecal contamination. The potential risk differential between human and selected non-human faecal sources has been characterized previously for direct deposition of animal feces to water. In this evaluation, we examine the human illness potential from a recreational exposure to freshwater impacted by rainfall-induced runoff containing agricultural animal faecal material. Risks associated with these sources would be at least an order of magnitude lower than the benchmark level of public health protection associated with current US recreational water quality criteria, which are based on contamination from human sewage sources. Highlights: We examine the human illness potential from exposure to rainfall-induced runoff. The predicted risks are lower than the benchmark level of protection. This risk assessment should be helpful to inform public health decision-making.